2003
DOI: 10.1074/jbc.m206328200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Dss1 as a 12-O-Tetradecanoylphorbol-13-acetate-responsive Gene Expressed in Keratinocyte Progenitor Cells, with Possible Involvement in Early Skin Tumorigenesis

Abstract: This study identifies genes expressed early in 12-Otetradecanoylphorbol-13-acetate (TPA)-induced skin carcinogenesis in genetically initiated Tg⅐AC v-Ha-ras transgenic mice. Keratinocyte progenitor cells from TPA-treated Tg⅐AC mice were isolated with fluorescence-activated cell sorting and expression was analyzed using cDNA microarray technology. Eleven genes were identified whose expression changed significantly in response to carcinogen treatment. Deleted in split hand/split foot 1 (Dss1) is a gene associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…Characterization of the endogenous DSS1 protein Previous studies have shown that endogenous human and mouse DSS1 cannot be detected by Western blotting, although both recombinant and yeast DSS1 are detectable by this method (Jantti et al, 1999;Marston et al, 1999;Wei et al, 2003;Gudmundsdottir et al, 2004;Isono et al, 2004;Sone et al, 2004). To detect endogenous human DSS1, we generated an anti-DSS1 antiserum against a full-length DSS1 GST-fusion protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterization of the endogenous DSS1 protein Previous studies have shown that endogenous human and mouse DSS1 cannot be detected by Western blotting, although both recombinant and yeast DSS1 are detectable by this method (Jantti et al, 1999;Marston et al, 1999;Wei et al, 2003;Gudmundsdottir et al, 2004;Isono et al, 2004;Sone et al, 2004). To detect endogenous human DSS1, we generated an anti-DSS1 antiserum against a full-length DSS1 GST-fusion protein.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, DSS1 (sem1p/RPN7) has been found to form a structural subunit of the 26S proteasome and is required for the structural integrity of the 26S proteasome (Isono et al, 2004;Sone et al, 2004). DSS1 has also been identified as a 12-O-tetradecanoylphorbol-13-acetate-responsive gene expressed in keratinocyte progenitor cells that may be involved in early skin tumorigenesis (Wei et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 11 genes were identified as either upregulated (nine genes, including galectin 7, nucleoside diphosphate kinase B, keratin 14, Dss1, and a double-strand break repair RAD21 homolog) or downregulated (two genes, including keratin 15 and apoliprotein E precursor) in CD34 þ cells from TPA-treated mice. Further characterization of Dss1 has revealed that (1) Dss1 is overexpressed in TPA-induced hyperplastic skin, papillomas, and cutaneous malignancies; (2) constitutive expression of Dss1 promoted cell proliferation and soft agar growth in preneoplastic epidermal cell lines, demonstrating in vitro transformation potential and defining a possible role for Dss1 in early TPA-induced neoplastic development (Wei et al, 2003).…”
Section: Cellular Aspectsmentioning
confidence: 99%
“…The advent and use of gene array technology has revealed TPA-inducible genes involved in the Tg.AC tumorigenic response (Wei et al, 2003). Ongoing studies continue to explore the role Dss-1, NDPK-B, and other genes involved in the early stage of neoplastic development and skin tumorigenesis.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation